Does CEO compensation reflect managerial ability or managerial power? Evidence from the compensation of powerful CEOs - Song, Wei-Ling; Wan, Kam-Ming (Journal of Corporate Finance, 2019)
This paper examines the relation between managerial power and compensation for Chief Executive Officers of S&P 500 companies from 1993 through 2012. We find that more-powerful CEOs earn more than less-powerful CEOs. We refer to this additional compensation as a “power premium” and investigate this power premium based on two competing views. The managerial ability view argues that the power premium compensates CEOs for their better managerial talent while the managerial power view argues that the power premium reflects the CEO's ability to extract excessive compensation. Overall, our results are more consistent with the managerial ability view. Empirically, we find that the power premium and the fraction of equity-based compensation are invariant to whether the CEO is newly hired or not. We also find that the likelihood of having an explicit employment contract is similar between new and incumbent CEOs.